PERANAN PT INTEGRASI TRANSIT JAKARTA DALAM PENGELOLAAN TAMAN LITERASI MARTHA CHRISTINA TIAHAHU JAKARTA SELATAN - Regia Nataya Depari; Nina Widowati (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2026)
This study aims to analyze the role of PT Integrasi Transit Jakarta in the management of Martha Christina Tiahahu Literacy Park, South Jakarta. Martha Christina Tiahahu Literacy Park is one of the public spaces developed as a facility for literacy, education, recreation, and social interaction for the community. This research focuses on the role of PT Integrasi Transit Jakarta as the managing entity of the literacy park. This study employed a qualitative approach with a descriptive method. Data were collected through in-depth interviews, field observations, and documentation. The research informants consisted of the management of PT Integrasi Transit Jakarta, park operational staff, and visitors. Data analysis was conducted through the stages of data reduction, data presentation, and conclusion drawing. The results of the study indicate that PT Integrasi Transit Jakarta has performed most of its roles in managing the literacy park quite well, particularly as an innovator, modernizer, pioneer, and implementer. PT Integrasi Transit Jakarta has successfully introduced the concept of a literacy park integrated with a transitoriented area, utilized technology in monitoring and service systems, and activated the park through various literacy programs and community collaborations. However, its role as a stabilizer has not been fully optimal, particularly in enforcing regulations and preventing vandalism on park facilities. Supporting factors in the implementation of PT Integrasi Transit Jakarta’s role include organizational characteristics and management characteristics. Meanwhile, inhibiting factors stem from environmental characteristics and worker characteristics. Based on these findings, the management of Martha Christina Tiahahu Literacy Park by PT Integrasi Transit Jakarta needs to be continuously improved through strengthening supervision, enhancing facility quality, and developing sustainable literacy programs to ensure that the park functions optimally as an educational and inclusive public space.